Export Intensity, Geographic Diversification and the Role of Public Support: The Evidence from Old and New Europe SMEs - Mariola Ciszewska-Mlinarič (Entrepreneurial Business and Economics Review, 2018)
Objective: The objective of the article is to investigate how public support (both financial and non-financial) affects the geographic scope and export intensity of SMEs originating from Old (EU15) and New Europe (the CEE12 region). In particular, the work considers the direct and indirect effects (via geographic scope) of public support on the export intensity of SMEs.